Physicochemical properties and antioxidant activities of tree peony (Paeonia suffruticosa Andr.) seed protein hydrolysates obtained with different proteases. (30th May 2021) - Wang, Ying-Ying; Wang, Chen-Ying; Wang, Shuang-Tong; Li, Ying-Qiu; Mo, Hai-Zhen; He, Jin-Xing
Highlights: Enzymatic hydrolysis disrupted the α-helices of tree peony seed protein. Alcalase had the strong hydrolytic ability for tree peony seed protein. Alcalase hydrolysate had well physicochemical properties. Alcalase hydrolysate exhibited superior antioxidant ability to TPSP. Abstract: The physicochemical and antioxidant properties of tree peony seed protein (TPSP) hydrolysates by Alcalase, Neutrase, Papain, Protamex, and Flavourzyme were investigated in this study. The physicochemical properties were characterized by SDS-PAGE, particle size distribution, fourier transform infrared and fluorescence spectroscopy etc. The antioxidant activities were determined by DPPH radical, ABTS radical, Fe 2+ chelating, and reducing power. The results showed five proteases produced hydrolysates with a significantly reduced average particle size, α-helices, and surface hydrophobicity compared to TPSP. Alcalase and Neutrase hydrolysis enhanced the nutritional value of the hydrolysates. Alcalase hydrolysates possessed the highest degree of hydrolysis (27.97%) and lowest molecular weight (<13 kDa) with average particle size (231.33 nm). Alcalase hydrolysate displayed the highest radical scavenging (DPPH IC50  = 0.18 mg/mL, ABTS IC50  = 1.57 mg/mL), Fe 2+ chelating activity (IC50  = 0.99 mg/mL), and reducing power (0.594). These results provide the fundamentals for TPSP hydrolysates as antioxidants to be employed in food industry or pharmaceutical industry.